PENGEMBANGAN KELEMBAGAAN PETANI USAHATANI PADI EKOSISTEM PASANG SURUT DENGAN SISTEM CORPORATE FARMING DI KABUPATEN OGAN KOMERING ILIR PROVINSI SUMATERA SELATAN - Aprini, Nisma; Sriati; Asmani, Najib; Maryadi (Agripita Publisher, 2017)
Study of farmer institutional development of rice farming with corporate farming system for the development of rice farming in Ogan Ogan Ilir South Sumatra Province. Tidal marsh land has increasingly important and strategic role for the development of agriculture, especially in support of national food security. This is caused by the potential and productivity of land and management technology is already available. Tidal swamp land area that has the potential for agriculture, especially plant in Ogan Ogan Ilir still provided quite extensive rice. The purpose of this paper to determine the potential for institutional development of farmers with corporate farming system. That rice farming tidal ecosystem can still be developed to improve the welfare of farmers, if the farmer institution transformed into institutional corporations (corporate farming). The study shows that institutional development with corporate farming system through business partnerships to increase production, productivity and ensures the creation of farm efficiency. To encourage institutional success with corporate farming system will require collaboration between government, private sector and farmers.